Palestinian-Jewish bilingual schools in Israel: Unravelling the educational model. (October 2019) - Meshulam, Assaf
Highlights: The article presents the education models that shaped Palestinian-Jewish ("PJ") bilingual education in Israel. A model of PJ education has emerged from the entanglement of different influences, contexts, and circumstances. PJ schools are constructed on an integration of progressive education, peace education, and two-way bilingual education. The PJ schools implement similar key strategies and practices to develop their curricula and pedagogy. The PJ model has been shaped by the unique circumstances of conflict-ridden Israeli society and its education system. Abstract: Palestinian-Jewish ("PJ") bilingual (Arabic-Hebrew) schools in Israel represent a unique educational model that has seen a modest growth in the Israeli education field over the last few decades. A variety of terms are used to define this educational model, including bilingual, binational, multicultural, and integrated, as well as a form of peace education and critical democratic education. This multiplicity of definitions reflects the fact that while all the PJ schools were founded on a fundamental ideological vision of shared education between Jews and Arabs, none was developed based on a clear bilingual, or any other single, educational model. This paper presents the different educational models that influenced the emergence and development of the PJ schools and proposes that despite the uncoordinated entanglement of influences, a certain model of PJ bilingual education can be identified. I suggest that all the schools share a similar integration of three primary educational approaches and implement similar key strategies and practices in developing their curricula and pedagogies. I claim that a central factor in this development is the unique circumstances of the Israeli education system and conflict-ridden Israeli society in which these schools emerged, developed, and have survived and the challenges they have had to contend with in this setting.